The ferric Iron uptake transcriptional regulator (Fur) governs virulence and stress responses in Listeria monocytogenes and serves as a target for novel food safety interventions - Aiyun Li; Haonan Xu; Ruofei Song; Ge Song; Arshad Qandeel; Qiyu Cao; Xiaohui Zhang; Tongxin Ge; Wenxin Wang; Yiyang Li; He Sun; Jinxuan Gui; et al. (Food Research International, 2026)

Bioaerosols in the atmospheric environment of oil exploitation sites: spatial and temporal distribution, sources, influencing factors, health risks, and reduction efficiency of masks - Hongjie Yang; Shen He; Zongting Yao; Hao Li; Qihao Feng; Simin Huang; Zhen Chen; Jiasheng Ni; Zhishu Liang (Environmental Pollution, 2026)

Willow-Leaf copper MOF networks for efficient oil-water separation and anti-microbial adhesion - Meng Xu; Simin He; Yu Wang; Lang Wei; Jinying Wang; Ruibin Guo; Nijuan Liu; Zunli Mo (Journal of Environmental Chemical Engineering, 2026)

The transcription factor SbWRKY6 confers cadmium tolerance via activating SbPLAC8–17 expression in sorghum - Shan Cao; Jiqing Zhang; Zhengyu Guo; He Wang; Zengting Chen; Simin Li; Na Sui (Journal of Hazardous Materials, 2026)

Advanced technologies for monitoring and control of booklice in the stored grain: A review - Rebecca Nyirahirwa; Yujie Lu; Simin Yao; Shams Fawki; Tianyu Sha; Zhuotong Lu; Sufen Cui; Peihuan He (Food Control, 2026)

Corrigendum to “Multimodal luminescence of CaZnGe2O6:Mn2+,Yb3+ phosphors for anti-counterfeiting: dynamic photoluminescence, afterglow, photostimulated luminescence, thermostimulated luminescence and mechanoluminescence” [Chem. Eng. J. 524 (2025) 169152] - Simin Yu; Yujia Gong; Guanlin He; Anfei Chen; Qiaoling Chen; Changkui Duan; Hai Guo (Chemical Engineering Journal, 2026)

Astronomical and volcanic forcing of Paleocene carbon cycle perturbations in the Norwegian Sea Basin - Xiaoyue Zhang; David B. Kemp; Manuel Vieira; David W. Jolley; Simin Jin; Qing Liu; Zixin He; Xilei Sun; Chunju Huang (Global and Planetary Change, 2026)

Complementary Protective Effects of Lactiplantibacillus Plantarum GUANKE and Picolinic Acid Against Influenza A Virus Infection in Mice - Jielan Mi; Kun Yue; Xiao Zhang; Yuewen Yang; Simin Lu; Yujia He; Zhihan Yang; Siqin He; Yuanming Huang; Liqiong Song; Zhihong Ren; Jianguo Xu (Probiotics and Antimicrobial Proteins, 2026)

Lactiplantibacillus plantarum GUANKE Alleviates Intestinal Barrier Damage Caused by Influenza Infection in Mice - Kun Yue; Simin Lu; Tao Yang; Jielan Mi; Siqin He; Hanyu Ma; Yujia He; Zhihan Yang; Yuanming Huang; Liqiong Song; Zhihong Ren; Lili Ren; et al. (Probiotics and Antimicrobial Proteins, 2026)

Amidoxime-modified PAN@Ce-UiO-66 nanocomposite fiber membrane for efficient removal of Cr(Ⅵ) from water - Yongzhang Qi; Hao Liang; Hebing Pei; Simin He; Hui Zhang; Shijing Li; Shikai Yu; Ruibin Guo; Nijuan Liu; Zunli Mo (Journal of Environmental Chemical Engineering, 2026)

Multimodal luminescence of CaZnGe2O6:Mn2+,Yb3+ phosphors for anti-counterfeiting: dynamic photoluminescence, afterglow, photostimulated luminescence, thermostimulated luminescence and mechanoluminescence - Simin Yu; Yujia Gong; Guanlin He; Anfei Chen; Qiaoling Chen; Changkui Duan; Hai Guo (Chemical Engineering Journal, 2025)

Development of fluorine-free superhydrophobic antibacterial and antifouling coatings: A multifunctional composite system for biomedical materials and metal protection - Meng Xu; Simin He; Yu Wang; Rongkai Li; Lang Wei; Ruibin Guo; Nijuan Liu; Zunli Mo (Chemical Engineering Journal, 2025)

Multi-asymmetry on residual sediment transport in the branching channels of the Yangtze Estuary - Simin Zhou; Chunyan Zhu; Jianliang Lin; Weiming Xie; Naiyu Zhang; Leicheng Guo; Qing He (Journal of Hydrology, 2025)

Water-stabilized perovskite CsPbBr3/CsPb2Br5 for high-sensitivity fluorescence “on-off-on” recognition and cell imaging - Simin He; Rongkai Li; Meng Xu; Yu Wang; Ruibin Guo; Nijuan Liu; Zunli Mo (Chemical Engineering Journal, 2025)

Melatonin protects bovine oocyte from βHB-induced oxidative stress through the Nrf2 pathway - Kaiyan Zhang; Jing Guo; Simin Wang; Changguo Min; Jun Wang; Hongyu Liu; Yi Fang; He Ding; Jing Zhao; Xin Ma; Wenfa Lu (Theriogenology, 2025)

Cerebrospinal Fluid-Derived extracellular Vesicle-Inspired Multifunctional bone regeneration scaffold for cranial defect repair - Jie He; Yifan Zhang; Xiaolan Sun; Minjie Wang; Qing Zhang; Simin Liu; Shaojie Yu; Xuan Wang; Zhenxing Wang; Junjun Li; Xiaobin Jiang (Chemical Engineering Journal, 2025)

Formation of flake-like DAAF crystals with tunable size realized on a microfluidic platform for binder-free initiator explosives - Bo Yang; Shengshu Xi; Simin He; Jin Chen; Wei Cao; Rui Li; Rupeng Bu; Xiaona Huang; Jincan Zhu; Qi Wu; Weimiao Wang; Xiaodong Li; et al. (Chemical Engineering Journal, 2024)

Potential retention of dissolved organic matter by soil minerals during wetland water-table fluctuations - Simin Wang; Ting Liu; Erxiong Zhu; Chen He; Quan Shi; Xiaojuan Feng (Water Research, 2024)

Efficient zero wastewater and salt-free of cotton fiber dyeing via hydrophobic organic chemical/water two-phase dyeing system - He Zhu; Liujun Pei; Jingyuan Yi; Simin Sun; Qiushuang Hu; Jiping Wang; Zongqian Wang (Journal of Cleaner Production, 2024)

Experimental study on the influence of inlet velocity and fuel/air ratio on outlet temperature profile performance in a turboshaft engine combustor - Ping Jiang; Simin Xiong; Wenzhuo Xu; Zhao Du; Xiaomin He (Fuel, 2024)

Pretreatment of Luzhou distiller’s grains for feed protein production using crude enzymes produced by a synthetic microbial consortium - Jixiang Liu; Shilei Wang; Zhi Wang; Caihong Shen; Dong Liu; Xiaojuan Shen; Longfei Weng; Yun He; Simin Wang; Jiaxin Wang; Wei Zhuang; Yafan Cai; et al. (Bioresource Technology, 2023)

Free nitrous acid prediction in ANAMMOX process using hybrid deep neural network model - Junlang Li; Jilan Dong; Zhenguo Chen; Xiaoyong Li; Xiaohui Yi; Guoqiang Niu; Jiaan He; Simin Lu; Yuxiang Ke; Mingzhi Huang (Journal of Environmental Management, 2023)

Occurrence and removal rate of typical pharmaceuticals and personal care products (PPCPs) in an urban wastewater treatment plant in Beijing, China - Jia Liu; Simin Ge; Peng Shao; Jianfeng Wang; Yanju Liu; Wei Wei; Can He; Lilan Zhang (Chemosphere, 2023)

Enhanced microbial contribution to mineral-associated organic carbon accrual in drained wetlands: Beyond direct lignin-iron interactions - Chengzhu Liu; Simin Wang; Yunpeng Zhao; Ya Wang; Yiyun Wang; Erxiong Zhu; Juan Jia; Zongguang Liu; Jin-Sheng He; Xiaojuan Feng (Soil Biology and Biochemistry, 2023)

Effects of gestational ambient extreme temperature exposures on the risk of preterm birth in China: A sibling-matched study based on a multi-center prospective cohort - Qiong Wang; Lina Yin; Haochen Wu; Zhoupeng Ren; Simin He; Aiqun Huang; Cunrui Huang (Science of The Total Environment, 2023)

Bioaugmentation of Cd(II) removal in high-salinity wastewater by engineered Escherichia coli harbouring EC20 and irrE genes - Simin Zong; Hui Yun; Xuan Yu; Yue He; Aman Khan; Haibo Tang; Si Li; Wenxue Wang; Xiangkai Li (Journal of Cleaner Production, 2023)

Multi-perspective synergistic construction of dual-functional heterostructures for high-temperature Li-S batteries - Yiding Li; Qiang Zhang; Simin Shen; Siqi Wang; Liangliang Shi; Dequan Liu; Yujun Fu; Deyan He (Chemical Engineering Journal, 2023)

Insights into methanogenesis of mesophilic-psychrophilic varied anaerobic digestion of municipal sludge with antibiotic stress - Hui Yun; Bin Liang; Zhangwei He; Minghan Li; Simin Zong; Zhenfei Wang; Bin Ge; Peng Zhang; Xiangkai Li; Aijie Wang (Journal of Environmental Management, 2023)

Effect of tornado near-ground winds on aerodynamic characteristics of the high-speed railway viaduct - Simin Zou; Xuhui He (Engineering Structures, 2023)

Planar D-σ-A type thermally activated delayed fluorescence material with Intra- and intermolecular charge transfer characteristics - Simin Jiang; Jianyin Lin; Deli Li; Mengke Li; Yanmei He; Wentao Xie; Jiting Chen; Yiyang Gan; Guo-Xi Yang; Zhihai Yang; Wei Li; Shi-Jian Su (Chemical Engineering Journal, 2023)

The catalytic mechanism of intercalated chlorine anions as active basic sites in MgAl-layered double hydroxide for carbonyl sulfide hydrolysis - Changming Li; Shuying Zhao; Xiaolong Yao; Li He; Simin Xu; Xianbao Shen; Zhiliang Yao (Environmental Science and Pollution Research, 2022)

Streptomyces luteolifulvus sp. nov., a novel actinomycete isolated from soil in Nanjing, China - Shanshan Zhao; Ming Cheng; Congyu Lin; He Liu; Zhengran Wang; Kai Zhang; Simin Song; Qian Yang (Antonie van Leeuwenhoek, 2021)

Dynamic relationship between meteorological conditions and air pollutants based on a mixed Copula model - Simin He; Zhiyao Li; Wenjie Wang; Mingxing Yu; Liangpo Liu; Md Nur Alam; Qian Gao; Tong Wang (International Journal of Climatology, 2021)
Many methods have been developed to verify the correlation between meteorological conditions and air pollutants; however, all have limitations that lead to biased or incomplete conclusions. Hence, improved methods are urgently required to describe this correlation comprehensively and accurately. In this study, we demonstrated the ability of the Copula function to apply time‐varying correlations between meteorological factors and atmospheric pollutants. A mixed Copula model was constructed using meteorological monitoring data for Beijing and Guangzhou from 2014 to 2019 to dynamically analyse the correlation characteristics and tail dependence between these factors. We then performed a correlation analysis for the data from the average, lower, and upper tails to obtain a more accurate and comprehensive correlation description. Dynamic analysis results demonstrated significant seasonal fluctuations between meteorological conditions and pollutants relationships. Moreover, the correlation coefficient variations differ according to their average and tail values. High humidity is more likely to be accompanied by increased NO 2 compared with average summer humidity. Our proposed model represents a novel application of the Copula function for determining the factors influencing air pollution. This model emphasizes the tail dependence between meteorological conditions and air pollutant concentrations and can be used to guide more targeted prevention and control strategies.

Genome-wide identification, characterization analysis and expression profiling of auxin-responsive GH3 family genes in wheat (Triticum aestivum L.) - Wenqiang Jiang; Junliang Yin; Haotian Zhang; Yiqin He; Simin Shuai; Shuhui Chen; Sunlin Cao; Wei Li; Dongfang Ma; Huaigu Chen (Molecular Biology Reports, 2020)

Impact of depositional environment and diagenesis on the Upper Triassic Xujiahe tight-sand reservoir in Guang’an area, Central Sichuan Basin, SW China - Dan He; Xinguo Duan; Simin Li; Bo Zhou; Honghui Wang; Yong Heng; Shuang Feng (Carbonates and Evaporites, 2019)

The protective microRNA-199a-5p-mediated unfolded protein response in hypoxic cardiomyocytes is regulated by STAT3 pathway - Yang Zhou; Bo Pang; Yingbin Xiao; Simin Zhou; Bin He; Fan Zhang; Wei Liu; Huali Peng; Peng Li (Journal of Physiology and Biochemistry, 2019)

An Improved “Dynamic Control Operation Module” for Cascade Reservoirs - Zhongbo Zhang; Xiaoyan He; Simin Geng; Shuanghu Zhang; Liuqian Ding; Guangyuan Kan; Hui Li; Xiaoming Jiang (Water Resources Management, 2018)